INTERFACE FRICTION OF SMOOTH GEOMEMBRANES AND OTTAWA SAND - Rustam Effendi (INFO-TEKNIK, 2011)
Geomembranes commonly used in civil engineering constructions are mostly in contact with soils. Some constructions failed due to slippage between geomembrane sheets and interfacing soils. This paper aims at presenting the interface strength of various geomembranes and Ottawa sand resulting from tests with the ring shear device. The interface strength is generally governed by the stiffness, the texture of geomembranes and the imposed stress level. It was found that residual friction angles, dresidual, for the interfaces varied from 10.5° to 28.1° or 0.34 to 0.97 in efficiency ratio. The lower value is for a smooth HDPE, the higher value is mobilised by a soft PVC at higher stresses.